Sintesis Zeolit dari Abu Layang dengan Metode Hidrotermal dan Uji Adsorptivitas Terhadap Logam Timbal (Pb) - Rismang, Rismang; Syamsidar HS, Syamsidar HS; Ramadani, Kurnia (Al-Kimia, 2017)
Synthesis of zeolite from fly ash obtained from Jeneponto Bosowa energypower plant have been conducted by hydrothermal method. This study was conducted to determine the characteristics of a synthetic zeolite fly ash and synthetic zeolite adsortivitas to metallic lead (Pb). Fly ash which is the main source of silica prepared by the process of concentration variations reflux with HCl (2M; 3M; 4M and 5M). Manufacture of sodium silicate solution by dissolving NaOH fly ash into the proportion of 10 ml per 1 gram of fly ash. Synthesis process by adding sodium aluminate into a solution of sodium silicate with a ratio of 1: 1 and then put in an autoclave as a hydrothermal process at a temperature of 120 ° C for 2 hours. Hydrothermal product obtained is characterized by X-Ray Diffraction (XRD) to determine the type and intensity of the zeolite crystals obtained from the synthesis process. XRD analysis results showed the highest intensities are in the process of reflux 5M with type zeolite obtained in the form of zeolite ITQ-34, zeolite (K, Ba) -G, L, sodalite and alumina-silica minerals such as eucryptit and aluminum oxide. The resulting zeolite able to absorb the metals Pb2+ at 99.04%, which is made with a concentration of 20 ppm of 50 mL with a mass of 1 gram of zeolite.